HIV-1 incidence and HIV-1 associated mortality in a cohort of urban factory workers in Tanzania. Issue 4 (August 1995) - Borgdorff, M W; Barongo, L R; Klokke, A H; Newell, J N; Senkoro, K P; Velema, J P; Gabone, R M
Abstract : OBJECTIVE--To determine HIV-1 incidence and HIV-1 associated mortality in a prospective cohort study. To determine whether the cohort is suitable for studies aiming to determine the impact of interventions on HIV-1 incidence. METHODS--The study population was a cohort of 1772 urban factory workers (1478 men and 294 women) in northwest Tanzania. The study took place from October 1991 to September 1993. Outcome measures were HIV-1 seroconversion and death. RESULTS--HIV-1 incidence was 1.2 (95% CI 0.7-2.0) per 100 person-years (pyr). Crude annual mortality was 4.9 per 100 pyr in those with and 0.3 in those without HIV-1 infection, giving an age and sex adjusted mortality ratio of 12.9 (95% CI 5.4-30.7). Of all deaths, 62% were attributable to HIV-1 infection. CONCLUSION--HIV-1 infection was a major public health problem, being the major cause of death in this adult population. At an HIV-1 incidence of 1.2 per 100 pyr, a large cohort size would be required to evaluate the impact of interventions on HIV-1 incidence.